Gender preference between traditional and PowerPoint methods of teaching gross anatomy - Saleh Nuhu; Lawan Hassan Adamu; Mohammed Alhaji Buba; Sani Hyedima Garba; Babagana Mohammed Dalori; Ashiru Hassan Yusuf (Wolters Kluwer Medknow Publications, 2018)
Introduction: Teaching and learning process is increasingly metamorphosing from the traditional chalk and talk to the modern dynamism in the information and communication technology. Medical education is no exception to this dynamism more especially in the teaching of gross anatomy, which serves as one of the bases of understanding the human structure. Objective: This study was conducted to determine the gender preference of preclinical medical students on the use of traditional (chalk and talk) and PowerPoint presentation in the teaching of gross anatomy. Subjects and Methods: This was cross-sectional and prospective study, which was conducted among preclinical medical students in the University of Maiduguri, Nigeria. Using simple random techniques, a questionnaire was circulated among 280 medical students, where 247 students filled the questionnaire appropriately. The data obtained was analyzed using SPSS version 20 (IBM Corporation, Armonk, NY, USA) to find the method preferred by the students among other things. Results: Majority of the preclinical medical students in the University of Maiduguri preferred PowerPoint method in the teaching of gross anatomy over the conventional methods. The Cronbach alpha value of 0.76 was obtained which is an acceptable level of internal consistency. A statistically significant association was found between gender and preferred method of lecture delivery on the clarity of lecture content where females prefer the conventional method of lecture delivery whereas males prefer the PowerPoint method, On the reproducibility of text and diagram, females prefer PowerPoint method of teaching gross anatomy while males prefer the conventional method of teaching gross anatomy. Conclusion: There are gender preferences with regard to clarity of lecture contents and reproducibility of text and diagram. It was also revealed from this study that majority of the preclinical medical students in the University of Maiduguri prefer PowerPoint presentation over the traditional chalk and talk method in most of the questions ask.